2004
DOI: 10.4067/s0716-078x2004000300013
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of habitat fragmentation on the abundance and species richness of beetles in experimental alfalfa micro-landscapes

Abstract: Habitat loss and fragmentation are considered as the main causes of biodiversity depression. Habitat loss implies a reduction of suitable habitat for organisms, and habitat fragmentation is a change in the spatial configuration of the landscape, with the remaining fragments resulting more or less isolated. Recent theory indicates that the effects of habitat loss are more important than those of habitat fragmentation, however there are few experimental studies evaluating both processes separately. To test the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
4
9
0
2
Order By: Relevance
“…In the long-term, these effects disappeared. These results are similar to those observed in a previous (independent) study with varying levels of habitat fragmentation and isolation in alfalfa, and a uniformly high level of habitat loss (84%) (Grez et al, 2004b;. In that study, the population abundance and species richness of carabids (and other beetles) were higher in the more fragmented landscapes, and also this effect disappeared later in the season.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the long-term, these effects disappeared. These results are similar to those observed in a previous (independent) study with varying levels of habitat fragmentation and isolation in alfalfa, and a uniformly high level of habitat loss (84%) (Grez et al, 2004b;. In that study, the population abundance and species richness of carabids (and other beetles) were higher in the more fragmented landscapes, and also this effect disappeared later in the season.…”
Section: Discussionsupporting
confidence: 81%
“…The increase in beetle species richness with increasing fragmentation is not an isolated result. It has been reported also for assemblages of endangered polyphagous butterflies in agricultural landscapes of Germany (Tscharntke et al, 2002), insects in grasslands in North America (Collinge & Forman, 1998), and beetles associated with alfalfa landscapes in Chile (Grez et al, 2004b). Furthermore, we have determined that native and exotic species of coccinellids did not segregate in different landscapes.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, in southeastern Sweden (Jonason et al 2010), butterfly species richness (not the abundance) was found to be positively related to increasing tree cover in the farm landscape. Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because fragmentation and loss of habitats are often strongly correlated (Fahrig 2003;Smith et al 2009) effects of fragmentation can be masked or enhanced by habitat loss and vice versa (Ewers and Didham 2006). The separation of fragmentation and habitat loss is becoming more and more popular in experimental model systems (Grez et al 2004;Zaviezo et al 2006;Diekötter et al 2007;Haynes et al 2007) but has rarely been achieved in landscape-scale studies (but see Brosi et al 2008;Farwig et al 2009;Holzschuh et al 2010;Bailey et al 2010). However, population and community ecology need a large-scale perspective because local patterns of biodiversity are influenced by the regional settings (McGarigal and Cushman 2002;Tscharntke and Brandl 2004).…”
Section: Introductionmentioning
confidence: 99%